ON THE NORMALITY OF SOME CAYLEY DIGRAPHS WITH VALENCY 2 - Mehdi Alaeiyan (Journal of the Indonesian Mathematical Society, 2011)
We call a Cayley digraph ????=Cay(G; S) normal for G if R(G), the rightregular representation of G, is a normal subgroup of the full automorphism groupAut(????) of ????. In this paper we determine the normality of Cayley digraphs of valency2 on the groups of order pq and also on non-abelian nite groups G such that everyproper subgroup of G is abelian.DOI : http://dx.doi.org/10.22342/jims.17.2.3.67-72